Sentiment Analysis of Simobi Plus Mobile Application Using Naïve Bayes Classification - Stevan Hamonangan Hardi; Kristoko Dwi Hartomo (Universitas Budi Darma, 2023)
Sinar Mas Bank is one of many banks operating in Indonesia. Quite a few people use Sinar Mas Bank's services as their bank of choice for their day-to-day transactions. By popular demand, Sinar Mas Bank serves users of banking services by creating an M-banking application. The M-banking application created by Bank Sinar Mas is called Simobi Plus Mobile Banking. There are already 52.3 thousand reviews regardings this application on the Google Play Store platform. Among these are positive and negative reviews from customers who use the application for their daily transactions. In reviews that use 1-5 star ratings, many people are misled by giving different ratings than the given stars. Many customers who leave 5-star app reviews, but comments on these reviews contain negative words. As a result, the application developer becomes confused because the comments given do not match the rating given by the user. Comments that are not in accordance with the rating given can involve the developer of the application to make improvements or development for the application. Therefore, Research should be conducted using techniques and analytics to categorize the user comments into several groups. This study uses sentiment analysis using the Naive Bayes method to capture positive and negative sentiments for comments on the Simobi Plus mobile banking application on the Google Play store, so that these sentiments have the appropriate value. The accuracy scores for the negative class, positive class, recall, and mood analysis are used to evaluate the test. The resulting value has an accuracy of 99%, which is almost perfect. The precision value was 100%, whereas the recall class produced a value of 98% (positive class: negative). And the AUC value is 0.980.